One step forward: a new multilingual MOOC on sociopragmatic skills for linguistic inclusion of migrants and refugees - Matteo Viale (Italiano a scuola)
This paper presents and discusses a recent tool for the linguistic integration of migrants and refugees: the MOOC One Step Forward, developed within the framework of the European project INCLUDEED. The MOOC is available in six languages (Italian, English, French, German, Portuguese, and Spanish) and is notable for its focus – through videos and online activities – on the communicative and pragmatically effective use of language, as well as on the learning of sociocultural information useful for everyday interaction, aspects often overlooked by more traditional tools.